Evaluasi Kondisi Simpang Tiga Tak Bersinyal (Studi Kasus: Jalan Cengkeh – Jalan Kalpataru – Jalan Dewandaru, Kota Malang) - Moni, Emanuel Yosef; Arifianto , Andy Kristafi; Rahma , Pamela Dinar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2024)
The purpose of this study was to evaluate the performance of a three-signal intersection located in Lowokwaru Subdistrict, Malang City, at Cengkeh Road, Kalpataru Road, and Dewandaru Road. This triangle suffers from congestion problems and long vehicle queues. The huge amount of traffic exceeds the capacity of the road, which causes a decrease in speed, longer delays, and many queues of vehicles. This research was conducted quantitatively using a descriptive approach. Data was collected through field surveys with direct observation and the use of tools such as research forms, watches, hand gauges, and digital cameras. Secondary data came from relevant institutions, such as the Central Bureau of Statistics (BPS) and the Malang City Transportation Office. In accordance with the Indonesian Road Capacity Guidelines (PKJI), the analysis was carried out by calculating traffic volume, road capacity, degree of saturation, delay, and queuing opportunities. The analysis shows that in the peak hour, this intersection has a degree of saturation (DJ) of 1,5, which far exceeds the PKJI required DJ < 0,85, and its level of service is classified as very poor. This performance degradation contributes to prolonged congestion and queuing in the area. To address this problem, a zebra crossing on Jalan Cengkeh and additional sidewalks at the intersection are recommended to reduce delay and improve intersection performance. This research is expected to provide practical solutions to improve traffic conditions at the intersection and reduce its negative impact on road users.